The Existence of Pesantren Traditions on Social Media: Content Strategy and Public Engagement on Instagram and TikTok An-Nur II Malang - Ainia Fikri Rahmawati; Khoirun Nisa'; Putri Silviana Safira; Abdul Fattah (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
This study explains the existence of pesantren tradition as represented through social media content, strategies for increasing public engagement, forms and levels of engagement, challenges and opportunities in maintaining the existence of the pesantren on Instagram and Tiktok An-Nur II Malang. Using a qualitative case study approach, data was collected through interviews, content observation, and literature review. Validity checked through triangulation, member checking, and referential adequacy check, then analyzed using the Miles & Huberman technique. Research findings show that the existence of pesantren tradition on An-Nur II Malang's social media is evident through content that represents scientific, ubudiyah, social traditions, and the five key elements of pesantren. Social media management is differentiated between formal and casual accounts through planning, production, evaluation, and optimization. Although there are challenges in maintaining consistency in production amid the students' density schedules, balancing content from non-official account, and adapting trends to pesantren values, opportunities arise through the utilization of pesantren traditions as a source of authentic content, institutional support, the potential of digital platforms, the capacity of multimedia team, and digital pesantren innovation. These findings provide references for other pesantrens in developing effective content and engagement strategies by leveraging opportunities within the pesantren environment.